What (If Anything) Do Satisfaction Scores Tell Us about the Intertemporal Change in Living Conditions - Christoph Wunder; Johannes Schwarze (Deutsches Institut für Wirtschaftsforschung (DIW), 2010)
This paper looks at the information content of satisfaction scores. It is argued that the information content depends on the extent to which people adapt to living conditions in general. Using data from the German Socio-Economic Panel Study (SOEP), the estimation of a dynamic panel data model provides evidence that adaptation takes place within a relatively short window of time: changes in living conditions are, for the most part, absorbed by an adjustment of the adaptation level within one year. This leads to the conclusion that the information content of satisfaction scores accentuates recent changes in living conditions. Remote changes are notcaptured by the according survey questions, even if these changes have long-term impact on living conditions. The usefulness of satisfaction scores as an indicator of people's living conditions is discussed.
Keywords: C23; I31; 330; adaptation; dynamic panel data model; subjective well-being; satisfaction; Zufriedenheit; Lebensqualität; Qualitative Methode; Informationswert; Panel; Deutschland